Pelatihan Safety Management System Bagi Personil Unit Penyelenggara Bandar Udara (UPBU) Di Indonesia - Tri Saputra, Surya; Sonhaji, Imam; Machmiyana, Ichyu; Arrafat, Bhima Shakti (Politeknik Penerbangan Indonesia Curug, 2023)
Every aviation service provider must establish, maintain and comply with a Safety Management System (SMS) that is appropriate to the size, nature and complexity of operations. One of the flight service providers is the Airport Management Unit (UPBU). Indonesia Curug Aviation Polytechnic conducts community service through online SMS training. The purpose of this activity is to equip participants with knowledge of the Safety Management System and be able to implement it in the world of work. Participants consisted of 22 people from UPBU throughout Indonesia, 1 person from the Directorate of Air Transport, 1 person from Aviation Facility Calibration Center and 1 person from the Airport Authority. Overall the activities ran smoothly and could be understood by the training participants. This is evidenced by the results of learning with an average grade of 81.05. Apart from that, the overall results are good. However, there is 1 (one) indicator that needs to be improved, namely internet connectivity. In online learning, one of the obstacles in its implementation is an internet connection. Moreover, the participants came from various regions in Indonesia.